Critical Discourse Analysis of Eminemâs âLove the Way You Lie Part IIâ - Arbain, Arbain (Teacher Training and Education Faculty, Widya Gama Mahakam Samarinda University, 2016)
This study is to analyze songs from Eminem which is related to his life story. In examining the songs, the researchers used the three inter-related processes of analysis tied to three inter-related dimensions of discourse proposed by Faicloughâs model of CDA. This study applied qualitative design with the content analysis approach. The analysis of this research focused on the words used such as African American Vernacular English variety, Informal language and American slang in the lyrics of the song Love The Way You Lie Part II and explain them. The result findings showed that there was a transcultural process or cross cultural in the song lyrics. There was a hiphop culture which was moved, changed and reused to create a new identity of the Eminem. There were 25 words and clauses of AAVE, 3 words of Informal language and 1 word of American slang language in the lyrics of the song of Love The Way You Lie.